2004
DOI: 10.1002/ijc.20222
|View full text |Cite
|
Sign up to set email alerts
|

Epstein‐Barr virus seroreactivity among unaffected individuals within high‐risk nasopharyngeal carcinoma families in Taiwan

Abstract: Most adults have been infected with EBV. Many studies have indicated that antibodies against specific EBV antigens, particularly IgA antibodies, can be predictive or prognostic of EBV-associated malignancies, such as NPC. We hypothesized that healthy individuals from families with a history of multiple members affected with NPC (who therefore might be genetically susceptible to NPC themselves) might have an EBV antibody profile that is distinct from that seen in healthy individuals from the community at large.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 39 publications
4
57
3
Order By: Relevance
“…Each study participant was asked to consent to the collection of 30 mL blood for genotyping and EBV antibody testing. Serum was tested for antibody titers to several anti-EBV antibodies known to be associated with NPC, including viral capsid antigen IgA, EBV nuclear antigen 1 IgA, and anti-DNase antibodies, according to the methods described previously (22). Individuals positive for any of these EBV markers were considered seropositive and individuals negative to all were classified as seronegative.…”
Section: Methodsmentioning
confidence: 99%
“…Each study participant was asked to consent to the collection of 30 mL blood for genotyping and EBV antibody testing. Serum was tested for antibody titers to several anti-EBV antibodies known to be associated with NPC, including viral capsid antigen IgA, EBV nuclear antigen 1 IgA, and anti-DNase antibodies, according to the methods described previously (22). Individuals positive for any of these EBV markers were considered seropositive and individuals negative to all were classified as seronegative.…”
Section: Methodsmentioning
confidence: 99%
“…The first was a casecontrol study, 20 and the second was a study of families with 2 or more affected members. 19,21 The 2 studies were conducted by the same collaborating institutions (the U.S. NIH and National Taiwan University) and used similar data collection instruments and testing methods. Human subject review committees in Taiwan and the United States approved both projects.…”
Section: Study Populationmentioning
confidence: 99%
“…Our data demonstrated that unaffected individuals from high-risk NPC families had elevated anti-EBV antibody titers compared to levels in the community at large. 19 In the current study, we evaluated EBV load in sera from unaffected individuals in high-risk NPC families. Our goal was to define the levels of EBV load that characterize this high-risk population using 2 different molecular assays.…”
mentioning
confidence: 99%
“…EBV enters B cells by interaction of the major glycoprotein gp350/220 (BLLF1) with CD 21 and then penetrates by the complex of viral glycoproteins gp25 (Pickard et al , 2004), gp42/38 and gp85 (gH) (Tao et al, 2006). Furthermore, EBV glycoproteins play important roles in humoral immune responses and sera against these proteins often neutralize virus.…”
Section: Introductionmentioning
confidence: 99%